Analysis of Public Policy and Criminal Law in The Perspective of Consumer Protection for Online Loan Users in Indonesia - Kalfin; Vimelia, Willen; Haq, Fadiah Hasna Nadiatul (Communication in Research and Publications (CRP), 2024)
The development of online loan services or pinjol in Indonesia raises new problems in consumer protection. Many cases of fraud and misuse of customer personal data are very concerning. The government has not had specific regulations regarding online loans. The existing regulations are merely appeals and suggestions for fintech pinjol to conduct business responsibly. In fact, stricter regulatory and enforcement steps are needed to address the increasing violations that harm consumers. This study aims to analyze public policies and criminal law in the perspective of protecting pinjol consumers in Indonesia. This research uses a normative legal approach with statute and conceptual approaches. The results are expected to provide recommendations for more effective legal protection for online lending consumers in Indonesia, as well as enriching academic literature on fintech and digital consumer protection. The conclusion is that firmer public policy and criminal law provisions are needed to protect consumer rights in using online loan services which currently have weak legal protection.